Nitrogen doped carbon nanodots as fluorescent probes for selective detection and quantification of Ferric(III) ions - Suk, Fun Chin; Tan, Shao-Chien; Suh, Cem Pang; Ng, Sing-Muk (Elsevier B.V., 2017)
Nitrogen (N) doped carbon dots (N-CDs) that showed blue fluorescence with quantum yield (QY) of 12.25% were synthesized by one step microwave irradiation of lysine in ortho-phosphoric acid at 1000 W for 5 min. The as-synthesized N-CDs were successfully explored as fluorescent probes for selective detection of ferric (Fe3+) ions in aqueous condition with a linear range from 0.2 to 5.0 mM and a detection limit of 0.074 mM ± 0.081 (S/N = 3). The N-CDs exhibited high selectivity towards the detection of Fe3+ ions even in the presence of interfering ions. The N-CDs also demonstrated the potential of practical application for determining of Fe3+ ions concentration in real samples with high recovery rate and low relative standard deviation error.